2011
DOI: 10.1091/mbc.e10-09-0741
|View full text |Cite
|
Sign up to set email alerts
|

CK1 activates minus-end–directed transport of membrane organelles along microtubules

Abstract: This study shows that the signal transduction pathway responsible for the initiation of minus-end–directed movement of membrane-bounded pigment granules in melanophores involves sequential activation of protein phosphatase 2A and casein kinase 1 and that this activation correlates with increased phosphorylation of the dynein intermediate chain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 56 publications
(92 reference statements)
2
32
1
Order By: Relevance
“…Still, the phenotype of fragmentation of perinuclear membrane-bound compartments by IC261 can be prevented by pre-treatment with taxol. However, interphase microtubules could be partially stabilized through pre- and co-treatment with taxol (figure 3), nevertheless our study also shows that in cells treated with taxol and IC261 MT dynamics are severely disturbed, and one cannot assume unaffected MT dynamics as suggested in a recent report [30]. In highly dynamic processes like the formation of mitotic spindles, neither pre- nor post-treatment with taxol could rescue the effect of IC261 on MTs (figure 5).…”
Section: Discussioncontrasting
confidence: 46%
“…Still, the phenotype of fragmentation of perinuclear membrane-bound compartments by IC261 can be prevented by pre-treatment with taxol. However, interphase microtubules could be partially stabilized through pre- and co-treatment with taxol (figure 3), nevertheless our study also shows that in cells treated with taxol and IC261 MT dynamics are severely disturbed, and one cannot assume unaffected MT dynamics as suggested in a recent report [30]. In highly dynamic processes like the formation of mitotic spindles, neither pre- nor post-treatment with taxol could rescue the effect of IC261 on MTs (figure 5).…”
Section: Discussioncontrasting
confidence: 46%
“…The enzyme responsible for phosphorylation in this system has not been identified; however, polo-like kinase (25) and casein kinase (26,27) have been reported to phosphorylate dynein IC in vitro and in Xenopus melanophores (27), and also activations of MAPK, CDK5, GSK3, and ROCK in NF1-KD PC12 cells were found in our previous study (7). Thus, these enzymes may be involved in the regulation of neurite outgrowth in NF1-KD cells.…”
Section: Discussionmentioning
confidence: 81%
“…69 Recently, it was shown that this control of directionality is mediated by phosphorylation of the dynein intermediate chain, where phosphorylating dynein apparently stimulates its activity. 70 This type of regulation has also been seen in Huntington’s disease, as one of the downstream effects of pathogenic huntingtin protein is kinesin phosphorylation, which appears to inhibit kinesin. 71 In addition, phosphorylation of the scaffolding protein JIP-1 modulates the directionality of Amyloid Precursor Protein (APP) motility in mouse axons.…”
Section: The Transport Complex In Vivo: Examining Organelles In LIVmentioning
confidence: 92%